171k views
4 votes
Y to the power of a times y to the power of a plus 2

User Tawni
by
5.1k points

1 Answer

5 votes

Multiplying monomials

To multiply two or more expressions with the same base, we add the exponents.

For example:


x^2\cdot x^3\cdot x^7=x^((2+3+7))=x^(12)

We are given the expression (in letters)


y^a\cdot y^(a+2)

Since both factors have the same base y, we have to add both exponents:


\begin{gathered} y^a\cdot y^(a+2)=y^(a+a+2) \\ \end{gathered}

Since a+a+2 = 2a+2:


y^a\cdot y^(a+2)=y^(2a+2)

User Gskalinskii
by
6.0k points